Experimental testing of the transverse horizontal axis water turbine - McAdam, R; Houlsby, G; Oldfield, M; McCulloch, M (2010)
This study outlines the procedures and results for a set of experiments on the transverse horizontal axis water turbine (THAWT), which is a variant of a Darrieus turbine. Testing of a 1/20th scale device was conducted in the combined wind, wave and current tank at Newcastle University. Flow depth and velocity were varied over a range of realistic Froude numbers for tidal streams. Various configurations of the device were tested to assess the merits of the THAWT design. Variants included a parallel-bladed device, a 'truss' device and a parallel-bladed device configured with blades pitched relative to the pitch circle tangent. Experiments were carried out using a speed controlled motor, allowing quasi-steady results to be taken over a range of tip speed ratios. The results demonstrate that, over a range of flow conditions, the device is capable of exceeding the Lanchester-Betz limit for kinetic efficiency. This is principally because of the relatively high blockage ratio that can be achieved with such a device. © 2010 © The Institution of Engineering and Technology.